Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1161/01.res.67.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex control of renal sympathetic nerve activity is potentiated at early phase of two-kidney, one-clip Goldblatt hypertension in conscious rabbits.

Abstract: Conscious normotensive and two-kidney, one-clip Goldblatt hypertensive rabbits were studied to determine the sensitivity of the arterial baroreflex control of renal sympathetic nerve activity (RSNA) and heart rate. The relations of the mean arterial pressure-RSNA and mean arterial pressure-heart rate were examined over a wide range of blood pressures produced by infusions of phenylephrine and nitroglycerin. The maximum slope obtained by logistic function analysis was considered to represent the baroreflex sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
32
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 37 publications
7
32
1
Order By: Relevance
“…1 In conscious rabbits with Ang II-dependent hypertension, the Ang II receptor antagonist [Sar 1 , Ala^Ang II not only reversed the high blood pressure but increased the maximum gain of the baroreceptor reflex control of renal sympathetic nerve activity (RSNA). 3 These data support the hypothesis that the antihypertensive effects of angiotensin converting enzyme (ACE) inhibitors are in part due to a centrally mediated decrease in sympathetic outflow. Because there are no in vivo studies on the Ang II receptor subtype that is functionally involved in the baroreceptor reflex, we compared the effects of angiotensin type 1 (AT^ and type 2 (AT 2 ) receptor antagonists on the baroreceptor reflex control of RSNA and heart rate (HR) in conscious spontaneously hypertensive rats (SHRs).…”
Section: Role Of Nitric Oxide and Angiotensin II In The Regulation Ofsupporting
confidence: 65%
See 1 more Smart Citation
“…1 In conscious rabbits with Ang II-dependent hypertension, the Ang II receptor antagonist [Sar 1 , Ala^Ang II not only reversed the high blood pressure but increased the maximum gain of the baroreceptor reflex control of renal sympathetic nerve activity (RSNA). 3 These data support the hypothesis that the antihypertensive effects of angiotensin converting enzyme (ACE) inhibitors are in part due to a centrally mediated decrease in sympathetic outflow. Because there are no in vivo studies on the Ang II receptor subtype that is functionally involved in the baroreceptor reflex, we compared the effects of angiotensin type 1 (AT^ and type 2 (AT 2 ) receptor antagonists on the baroreceptor reflex control of RSNA and heart rate (HR) in conscious spontaneously hypertensive rats (SHRs).…”
Section: Role Of Nitric Oxide and Angiotensin II In The Regulation Ofsupporting
confidence: 65%
“…II-dependent hypertensive rabbits. 3 We have recently demonstrated that the baroreceptor reflex control of RSNA and HR is blunted in conscious SHRs compared with age-matched Wistar-Kyoto rats. 8 Moreover, in the latter study, 8 long-term treatment with lisinopril substantially enhanced the maximum gain of the baroreceptor reflex in SHRs.…”
Section: ^Imentioning
confidence: 94%
“…Sustained decreases in A ltered central sympathetic outflow and decreased reflex control of peripheral sympathetic nerves are thought to be associated with established hypertension 14 ; however, the distinction between cause and effect is unclear. 5 - 6 The sympathetic nervous system could influence blood pressure control not only by its effect on the regulation of peripheral resistance but also by controlling volume homeostasis via efferent renal sympathetic nerve activity (RSNA). 7 -8 It is well established that RSNA influences tubular water and sodium reabsorption independent of changes in intrarenal and systemic hemodynamics.…”
Section: Impaired Cardiovascular Reflexes Precede Deoxycorticosteronementioning
confidence: 99%
“…- 6 The sympathetic nervous system could influence blood pressure control not only by its effect on the regulation of peripheral resistance but also by controlling volume homeostasis via efferent renal sympathetic nerve activity (RSNA).…”
mentioning
confidence: 99%
“…In the first, the baroreflex curve is shifted or reset to a higher pressure, whereas in the second there is a decreased sensitivity of the reflex as measured by a decreased slope (or attenuated gain) of the baroreflex curve. These mechanisms have been documented in many experimental animal models of hypertension (10,17,25,26).…”
mentioning
confidence: 93%